Mapping the Country’s Dependence on Indonesia’s Coal Import Market - MANURUNG, Riski Nurul Hasanah; PRAKOSO, Havidz Ageng; ROZIQIN, Ali (Theoretical and Practical Research in Economic Fields; Vol 15 No 1 (2024): TPREF, Volume XV, Issue 1(29), Spring 2024, 2024)
Indonesia is one of the world's largest producers and exporters of coal. Its strategic geographical location facilitates coal export activities to consumer countries. In addition, the quality of Indonesian coal is also very suitable for steam power plants, especially sold at competitive prices on the international market. This research highlights how the world's largest coal-importing countries depend on the Indonesian coal import market. This means that Indonesian coal significantly influences the world's energy contribution. Based on this fact, the author states that the coal that Indonesia exports to importing countries dramatically affects the economic conditions of these countries. Driven by population increases, economic expansion, improved quality of life, and energy use, coal is an important energy source. Therefore, many countries import coal to meet domestic energy needs and reserve coal supplies long-term. To find out this, the author uses a qualitative research method, descriptive analysis with a dependency theory approach, that is analyzed in a world macro context using a world system perspective. In addition, the author also uses mean calculations to find the average result of the amount of coal imports for each country.